Effect of Different Calcium Salts on Calcium Carbonates Formation Induced by Halophilic Bacillus oceanisediminis CB1 - Chintan Bhagat; Sunil Bhavsar; Rajesh Patel; Anjana Ghelani; Pravin Dudhagara; Rajesh Chaudhari (Acta Chimica Asiana, 2022)
Biomineralization through the biomimetic CO2 sequestration process has been gaining attraction in recent years due to the formation of carbonates widely used as raw material in various industrial processes. The deposition and dissolution of calcium carbonate can be affected by physiochemical factors, such as the type of calcium salt. However, most studies have focused on calcium chloride (CaCl2). In the present study, A potent bacterial carbonic anhydrase (CA) producer, Bacillus oceanisediminis CB1, was screened on CA activity from mangrove plant Avicennia marina, collected from Ghogha, Bhavnagar, India (21.68°N 72.28°E). We premeditated deposition experiments to determine the effects of different calcium salts on calcium carbonate deposition in Bacillus oceanisediminis CB1 colonies. The results demonstrated the calcite formation observed in calcium salt-supplemented nutrient agar, calcium chloride, and calcium acetate. Merely uniform distribution and peripheral distribution of calcite particles found in calcium acetate and calcium chloride supplemented into nutrient agar, respectively. Calcite formation was confirmed by staining with Alizarin Red S dye followed by  SEM-EDX. This study will provide a vital reference for designing and applying microbial-induced carbonate precipitation using different calcium salts.